Frank Reade, Jr.'s Search for the Silver Whale : Or, Under the Ocean in the Electric "Dolphin" - Senarens, Luis, 1863-1939 (Salt Lake City, UT : Project Gutenberg, 2017)
"Frank Reade, Jr.'s Search for the Silver Whale" by Luis Senarens is a novel written in the early 20th century. The story follows the adventures of a remarkable young inventor, Frank Reade, Jr., as he endeavors to construct a submarine vessel named the Dolphin. Together with his friend George Stanhope, they embark on a quest to capture a legendary silver whale, which is tied to a tragic tale of injustice concerning Stanhope's acquaintance's brother, whose innocence needs to be proven. At the start of the narrative, we are introduced to Frank Reade, Jr. and George Stanhope, who engage in a lively discussion about the feasibility of building a submarine boat. As they devise their plans, they enlist the help of Frank's loyal companions, Barney and Pomp, and set about constructing the Dolphin. The opening chapters establish the context for their adventure, revealing the motivations behind their expedition, such as recovering lost evidence that could free an innocent man from imprisonment. The excitement quickly escalates as they complete the submarine and prepare for an underwater journey filled with unforeseen dangers, illustrated by encounters with sharks and the intriguing prospects of the ocean depths. (This is an automatically generated summary.)
Release date is 2017-09-16
E-text prepared by Richard Tonsing and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Science fiction; Submarines (Ships) -- Fiction; American fiction -- 19th century; Adventure stories; Dime novels; Inventors -- United States -- Fiction; Popular literature -- United States